1980
DOI: 10.1111/j.1365-2362.1980.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced release of pancreatic polypeptide and its inhibition by propranolol: evidence for adrenergic stimulation

Abstract: Pancreatic polypeptide (PP) has been considered to be predominantly under cholinergic-vagal control and may therefore serve as an indicator of vagal tone. We found similar basal plasma concentrations of PP in athletes with bradycardia and in untrained subjects. We further observed that physical exercise--an adrenergic situation--induces a several-fold rise in PP plasma concentration. Maximal plasma PP levels correlated positively with maximal blood pressure. The exercise-induced rise of PP was completely aboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
2

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
3
9
2
Order By: Relevance
“…In general, adequate cholin ergic tone is almost indispensible for the se cretory activity of the PP cell: not only stim ulation of PP release by mechanisms that involve activation of the vagal nerves (e.g. sham feeding, insulin hypoglycemia) is atro pine sensitive [9,[11][12][13], but also the re sponse to food [7], histamine [24], gastroin testinal hormones [25,26], and adrenergic stimulation [27], and this strong cholinergic activity is also necessary under in vitro con ditions [9,28], Recently, it has been reported that adren ergic mechanisms contribute to the rnodula-tion of PP secretion; PP levels increased dur ing exercise [17,18,29] and p-sympathomimetics [30], The stimulatory action of cate cholamines is preserved in vitro [31]. It has been shown by Kronborg et al [32] and Christensen and Stadil [33] that stimulation of gastrin release during insulin hypoglyce mia involves adrenergic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In general, adequate cholin ergic tone is almost indispensible for the se cretory activity of the PP cell: not only stim ulation of PP release by mechanisms that involve activation of the vagal nerves (e.g. sham feeding, insulin hypoglycemia) is atro pine sensitive [9,[11][12][13], but also the re sponse to food [7], histamine [24], gastroin testinal hormones [25,26], and adrenergic stimulation [27], and this strong cholinergic activity is also necessary under in vitro con ditions [9,28], Recently, it has been reported that adren ergic mechanisms contribute to the rnodula-tion of PP secretion; PP levels increased dur ing exercise [17,18,29] and p-sympathomimetics [30], The stimulatory action of cate cholamines is preserved in vitro [31]. It has been shown by Kronborg et al [32] and Christensen and Stadil [33] that stimulation of gastrin release during insulin hypoglyce mia involves adrenergic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…After a basal period of 30 min 11 subjects underwent a physical exercise on a bicycle-ergometer for 15 min, as described previously by Feurle et al [3] with slight modifications. The subjects remained in a horizontal position during the whole test procedure.…”
Section: Physical Exercisementioning
confidence: 99%
“…The radioimmunoassay for PP was performed as published [12], insulin was determined with the RIAgnost insulin, cross-reacting about 5% with proinsulin (Behringwerke, Marburg). As canine PP and insulin were not available, serial dilutions of canine pan creatic extracts were placed in the radioimmunoassay for the respective hormones.…”
Section: Methodsmentioning
confidence: 99%